Foods of Korea - Sheen, Barbara; Gale Group (Detroit, Mich. KidHaven Press, 2011)
Explores the foods, cooking traditions, customs, eating habits, and food sources of Korea. Topics include favorite dishes, snacks and sweets, traditional holiday meals, and the preparations and traditions associated with these foods.
The heart of Korean cooking -- A delicious balance -- A snacker's paradise -- Meaningful foods.
Electronic reproduction.
Keywords: Cooking, Korean -- Juvenile literature; Korea -- Social life and customs -- Juvenile literature; Electronic books